2018
DOI: 10.17582/journal.pjz/2018.50.3.sc1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chihua Pumpkin Residue (Cucurbita argyrosperma) in Ruminal Gas Production and Digestibility in vitro

Abstract: This study was conducted to evaluate the effect of chihua pumpkin (Cucurbita argyrosperma) residue in ruminal digestibility and gas production in an in vitro assay. Four treatments were evaluated: a control using a standard diet for ruminants elaborated with corn stover, corn grain and soybean meal, and three experimental diets with 10, 20 and 30% dry residue of chihua pumpkin instead of corn stover. Dry matter digestibility and gas production was determined at 24 h of incubation in ruminal fluid obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Regarding the fruit, Dorantes et al [58] mention that the dry residue of Cucurbita argyrosperma (peel and pulp only) has low protein content (<9%) but contains almost 50% of neutral detergent fiber and 40% of acid detergent fiber, which makes it suitable for the formulation of diets for dairy cattle and rabbits. On the other hand, Crosby et al [71] mention that the ruminal digestibility of dry matter increases 21% by replacing up to 30% of corn stubble with dry residue of Cucurbita argyrosperma ; however, the digestibility of neutral detergent fiber decreases 7%, which is attributed to the degradation of nonfibrous carbohydrates such as sugars, which are rapidly fermented. Possibly, the sugar content is one of the reasons why the incorporation of pumpkin improves the palatability of the diet [72].…”
Section: Impact On Livestock Nutrition and Productivitymentioning
confidence: 99%
“…Regarding the fruit, Dorantes et al [58] mention that the dry residue of Cucurbita argyrosperma (peel and pulp only) has low protein content (<9%) but contains almost 50% of neutral detergent fiber and 40% of acid detergent fiber, which makes it suitable for the formulation of diets for dairy cattle and rabbits. On the other hand, Crosby et al [71] mention that the ruminal digestibility of dry matter increases 21% by replacing up to 30% of corn stubble with dry residue of Cucurbita argyrosperma ; however, the digestibility of neutral detergent fiber decreases 7%, which is attributed to the degradation of nonfibrous carbohydrates such as sugars, which are rapidly fermented. Possibly, the sugar content is one of the reasons why the incorporation of pumpkin improves the palatability of the diet [72].…”
Section: Impact On Livestock Nutrition and Productivitymentioning
confidence: 99%
“…( Cogan and Jordan, 1994 ) in the presence of a higher quantity of fermentable sugars and water-soluble carbohydrates in pumpkin ( Halik et al, 2018 ). Consequently, several reports have indicated that the presence of high water-soluble carbohydrate content following the inclusion of pumpkin increases the rumen-simulated DM fermentation by 26.5% with pumpkin inclusion in sorghum silage at 40% DM ( Forwood et al, 2021 ), effective degradability in an in situ system by 13.8% w pumpkin inclusion in sorghum silage at 40% DM ( Forwood et al, 2020 ), and IVDMD by 21 and 15.6% with pumpkin inclusion at 30% DM and 40% DM, respectively ( Crosby-Galván et al, 2018 ; Forwood et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Silages supplemented with vegetables favor the growth of Lactobacillus spp., simultaneously increasing the microbial diversity with sorghum, while maintaining in vitro fermentation and gas parameters [mL/g DM gas; percent, mg/g DM; mg/g CH 4 digestible dry matter (DMD)] with maize ( Forwood et al, 2019 ; Hooker et al, 2019 ). Moreover, in vitro studies have also utilized pumpkin ensiled at 30% DM with corn stover, which increased in vitro DM digestibility by 25%, while consequently decreasing gas production by 6% ( Crosby-Galván et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the increasing demand of food from animal origin [5], it is primordial to search for feed alternatives for livestock in order to diminish feed-food competition [8,9]. Our previous studies [13,16,17] and others [43] have described the potential of CR for animal feeding. We demonstrate that CR can be ensiled, and despite the technical limitations, this is the first pilot study in vivo suggesting that CR is accepted by cattle and does not modify milk production or composition in cows in a dual-purpose system.…”
Section: Experiments 3 Evaluation Of Cucurbita Argyrosperma Huber Silmentioning
confidence: 99%
“…Nonetheless information regarding the use of Cucurbita argyrosperma Huber in animal feed is still scarce. However, in an in vitro study it was shown that the dry residue of this pumpkin improves the degradability of dry matter (DM) in diets with high forage content [17].…”
Section: Introductionmentioning
confidence: 99%